Remote detection of ragweed (Ambrosia artemisiifolia L.) - Plaščak, Ivan (Array, 2018)
The paper presents the contemporary findings of remote sensing regarding the control of common ragweed on agricultural land. The two-year research was performed in co-operation with the company Ciklonzacija Ltd., Serbia. The remote sensing process starts with the collection of images captured by several types of cameras equipped with special filters. Images are obtained by modified cameras mounted on helicopters, drones, and airplanes. Next, a special software is used to produce maps based on the obtained images that show the level of weed spread on agricultural land, illegal waste dumping areas, and other uncultivated areas, i.e. the areas that are potential sources of ragweed spread. The maps have a considerable economic benefit when mapping agricultural, wood, and other areas. Moreover, they reduce the use of human resources, and increase the capacity of data acquisition as well as the accuracy of the model of weed spread and its control.